Serological Analyses of Cellular Slime Mold Development II. Preferential Loss, During Morphogenesis, of Antigenic Activity Associated with the Vegetative Myxamoebae - Sonneborn, D. R. (1965)
Sonneborn, D. R. (Brandeis University, Waltham, Mass.), L. Levine, and M. Sussman. Serological analyses of cellular slime mold development. II. Preferential loss, during morphogenesis, of antigenic activity associated with the vegetative myxamoebae. J. Bacteriol. 89:1092–1096. 1965.—A major antigenic component of Dictyostelium discoideum (vegetative myxamoebae) is retained during morphogenesis up to the final stages of fruiting-body construction. It is found in the cells constituting the stalk of the mature fruit but is undetectable in the spores. The nature of the preferential loss of antigen from this cell contingent is unknown. Antiserum prepared against the vegetative myxamoebae is cytotoxic and reduces cell viability by several orders of magnitude at dilutions of about 1:100.